HERBAL APPROACH FOR INDUCING MULTIPLE FOLLICULAR DEVELOPMENT IN CROSSBRED COWS - KUMAR , S SATHESH; PUNNIAMURTHY, N (The Indian Journal of Animal Reproduction, 2023)
The objective of the study was to assess the efficacy of fresh indigenous herbs in inducing multiple follicular development in crossbred cows. Healthy and regularly cyclic crossbred cows (n=6) were utilized for the study. As a control study, PGF20 (25 mg; IM) was administered to all the cows on Day 14 (Day 0-estrum) of the cycle. In the subsequent natural cycle, fresh wet mash of Mi.Jrraya koenigiileaves (200- 300 g /day) and Pedalium murex (50 g /day) were administered daily (per os) in equally split doses at-12 h interval, for seven days starting from Day 9 of the cycle. Sap of Aloe vera leaves (100 g; per os; b. i.d) was administered for the first two days and PGF 2 " (25 mg; IM) was administered on the penultimate day (Day 14) of herbal treatment. The ovarian status was assessed ultrasonically.for the presence of large follicles(.::: 9 mm) on the day of PGF 2 a induced estrus in both control and herbal treated cycles. All the animal.s ( 100%) responded for the herbal treatment with 2 large follicles. The mean numbers of large follicles on the day of induced estrus in control and treated cycles were 1.25 .:!:. 0.50 (1-2) and 3.67 ± 1:37 (2-5) respectively with a mean diameter of 10.11.±.0.40 mm and 9.38± 0.31 mm respectively. from the study it was evident that the multiple follicular development could be effectively achieved using the above combination of herbs.